Successful Treatment of Fibrosing Cholestatic Hepatitis Following Kidney Transplantation With Allogeneic Hematopoietic Stem Cell Transplantation: A Case Report. Issue 5 (February 2015) - Li, Dong Liang; Fang, Jian; Zheng, Zhiyong; Wu, Weizhen; Wu, Zhixian
Abstract : Abstract: Fibrosing cholestatic hepatitis (FCH) is an uncommon complication of renal transplantation and usually associated with hepatitis B and C viral infection. Without treatment, the prognosis is usually fatal within weeks of onset. There was rarely report with successful treatment intervention. This case report describes a uremic patient with HCV infection who developed a fatal form of FCH after kidney transplantation. This is the first reported successful case with allogeneic hematopoietic stem cell transplantation (AHSCT) without ablative conditioning. A dramatic virologic and clinical improvement was observed in this post-transplantation patient. But no adverse events related to AHSCT were observed. The patient returned to work full-time at 10 months of hospitalization and is still in good health by now. Serum HCV RNA gradually decreased from 2.5 × 10 6  Copies/mL at day 1 to 3.2 × 10 4  Copies/mL at day 98 and became negative (<400 Copies/mL) at day 126 of hospitalization and remains negative at the last available assessment. Our report suggests that allogeneic HSCT may have a therapeutic role in FCH.